2015
DOI: 10.1080/15332640.2015.1022628
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of health-related quality of life in Thai patients with alcohol dependence

Abstract: This study aimed to examine the correlates of health related quality of life in Thai patients with alcohol dependence. The amount of alcohol intake was calculated by timeline followback chart and the health related quality of life was determined by Short Form-36 Health Survey. The means of the Short Form-36 Physical Component and Mental Component Summary were 67.43 (18.74) and 64.45 (20.90), respectively. Stepwise linear regression models showed the number of heavy drinking days was significantly correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…Alkol bağımlıların-da yapılan bir çalışmada, bağımlıların SF-36 yaşam kalitesi alt grup puanları kontrol grubuna göre birçok alanda daha düşük bulunmuştur (13,14) . Alkol-madde bağımlılığında sağlık hizmetlerinden daha fazla yararlanıldığı bildirilmiştir (15) .…”
Section: Alkol Bağımlılığında Yaşam Kalitesiunclassified
See 2 more Smart Citations
“…Alkol bağımlıların-da yapılan bir çalışmada, bağımlıların SF-36 yaşam kalitesi alt grup puanları kontrol grubuna göre birçok alanda daha düşük bulunmuştur (13,14) . Alkol-madde bağımlılığında sağlık hizmetlerinden daha fazla yararlanıldığı bildirilmiştir (15) .…”
Section: Alkol Bağımlılığında Yaşam Kalitesiunclassified
“…Alkol bağımlılarında yaşam kalitesi hem yoğun alkol alımı sırasında hem de takip eden tedavi döneminde sıklıkla bozulmaktadır (2,14,16) . Bağımlılığın yol açtığı hastalıklar, kişilik bozukluğu ve psikiyatrik bozukluklar, iş kaybı ve zayıf iş performansıyla ilişkili olarak azalan sosyoekonomik statü ve psikiyatrik hastalıklar ile ilişkili zayıf duygusal durumlar, yaş ve cinsiyet alkol-madde bağımlılarında yaşam kalitesi için birer risk faktörü olarak belirtilmiştir (14,16,17) .…”
Section: Alkol Bağımlılığında Yaşam Kalitesiunclassified
See 1 more Smart Citation
“…Accumulated research evidence has shown that AUD impairs QOL and causes faculty loss. Many studies found that AUD patients reported poorer QOL compared with the general population (3)(4)(5)(6)(7), particularly in the emotional (8)(9)(10)(11)(12), mental health (13,14) and social functioning domains (11). However, the scores in the physical functioning domain were not significantly different between the AUD patients and the reference population (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have also revealed that AUD is a risk factor (15,16) or even a primary cause of low QOL (17), which means that AUD might be used to predict subsequent QOL. Moreover, evidence indicated that the higher alcohol consumption or longer heavy drinking days, the lower levels of QOL (5,18,19). Importantly, studies have reported that alcohol abstinence and its maintenance could improve QOL in AUD patients (8,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%